Professional and personal competency development in near-peer tutors of gross anatomy: a longitudinal mixed-methods study - Alvarez, Simone; Schultz, Jobst-Hendrik (Anatomical sciences education, 2019)
There are many benefits to peer and near-peer tutoring. The current literature suggests that near-peer teaching within the domain of gross anatomy may lead to the development of numerous competencies for burgeoning medical professionals. The aim of this study was a quantitative and qualitative approach to explore which professional and personal competencies anatomy tutors developed as a result of their teaching activities in a gross anatomy course at a medical school in Germany. For a period of 18 months, 24 peer tutors were followed and queried multiple times via questionnaire and semi-structured interviews. It was found that most of the skills tutors developed or strengthened over one semester matched most of the core competencies described in various official competency frameworks used for physician education. In particular, tutors thought that tutoring gross anatomy had improved their knowledge of professional behavior as well as their communication skills. They also felt that they had learned to take on more responsibility and to use available resources more effectively. Overall, tutoring gross anatomy was perceived as very challenging, but also very rewarding, mainly because it provided the opportunity to develop and strengthen important skills such as self-confidence, self-awareness, positive thinking, self-insight, and stress management. Ultimately, these are all factors that contribute to resilience, an important attribute for physicians.
First published: 15 May 2018
Gesehen am 16.07.2019